Early tibial subchondral bone texture changes after arthroscopic partial meniscectomy in knees without radiographic OA: A prospective cohort study - Wolski, Marcin; Thorlund, J.B.; Stachowiak, Gwidon; Holsgaard-Larsen, A.; Creaby, M.W.; Jørgensen, G.M.; Englund, M.; Podsiadlo, Pawel (WILEY, 2020)
Arthroscopic partial meniscectomy (APM) may lead to changes in underlying trabecular bone (TB) structure potentially promoting the development of knee joint osteoarthritis. Our aim was to investigate if there are early changes occurring in tibial subchondral TB texture in the leg undergoing medial APM compared with the unoperated non-injured contra-lateral leg. The bone texture was measured as the medial-to-lateral ratio of fractal dimensions (FD) calculated for regions selected on weight-bearing anteroposterior tibiofemoral x-rays. Twenty-one subjects before and 12 months after APM were included from 374 patients scheduled for unilateral medial APM. The medial-to-lateral ratio was calculated for horizontal, vertical, and roughest FDs respectively. Higher FD means higher bone roughness. Each FD was calculated over a range of scales using a variance orientation transform method. Mean values of medial-to-lateral horizontal FD calculated for APM knees at follow-up were higher than those at baseline. For unoperated knees the values were lower. The difference in the horizontal FD change from baseline to follow-up between APM and contra-lateral legs was 0.028 (95% CI, 0.004-0.052). The bone roughness changes may reflect the increase in peak knee adduction moment (KAM) and KAM impulse during walking reported for the same cohort in a previous study. They may also reflect early signs of osteoarthritis development and thus, we speculate that individuals with increased bone texture roughness ratio after APM might be at higher risk of knee osteoarthritis development.